NURSING AND GLOBALIZATION: THE INTERSECTION OF SOLIDARITY AND INTERDISCIPLINAR PRACTICE - Maria Helena Lenardt; Elis Rejane da Maia (Universidade Federal do Paraná, 1998)
It is a thought-provoking paper about the globalization process and nursing. It aims to contribute, contextually, for a more understanding, comprehensive and humanized professional practice. That is an issue which constantly demands interchange among several world views, supported by an interdisciplinar approach, favoring the understanding of other ways of viewing life and progress, facing the human being in need of professional help in a globalized world.